Current research in Egyptology 2018 : proceedings of the Nineteenth Annual Symposium, Czech Institute of Egyptology, Faculty of Arts, Charles University, Prague, 25-28 June 2018 - Hlouchová, Marie Peterková,; Belohoubková, Dana,; Honzl, Jirí,; Nováková, Věra, 1928- (Access archaeology., 2019)
'Current Research in Egyptology 2018' is a collection of papers and posters presented at the nineteenth symposium of the prestigious international student conference, held at the Faculty of Arts, Charles University in Prague on 25th-28th June, 2018.